Countrywide Corchorus olitorius L. core collection shows an adaptive potential for future climate in Benin - Tchokponhoué, Dèdéou A.; N’Danikou, Sognigbé; Omondi, Emmanuel; Coffi, Spéro; Sossou, Belchrist Eliel; Houdegbe, Aristide Carlos; Adje, Charlotte A. O.; Fassinou Hotegni, Nicodeme V.; Schranz, M. Eric; van Zonneveld, Maarten; Achigan-Dako, Enoch G. (Frontiers in Plant Science, 2025)
IntroductionUnderstanding the genome-wide variation pattern in crop germplasm is required in profiling breeding products and defining conservation units. Yet, such knowledge was missing for the large germplasm collection of Corchorus olitorius in Benin at CalaviGen (the University of Abomey-Calavi genebank), the world’s largest holder of the crop germplasm with 1,566 accessions conserved.MethodsUsing 1,114 high-quality SNPs, this study: i) investigated the spatial variation of the genetic structure of 305 accessions sampled along the South-North ecological gradient of Benin, ii) derived a core collection from the batch of accessions and iii) gauged the extent of (mal)adaptation of this core set.Results and discussionOverall, we detected a moderate diversity with a total gene diversity of 0.28 and an expected heterozygosity estimate of 0.27. The spatial variation of the genomic diversity painted an increasing trend following the South-North ecological gradient, giving rise to four optimal genetic groups based on STRUCTURE analysis while the neighbour-joining analysis revealed three clusters. The ShinyCore algorithm application yielded a core set of 54 accessions that echoed a good geographical representativeness and encompassed a level of diversity comparable to that of the whole collection. Nearly 88% of this core set accessions were characterized by a low genomic offset score, which suggests a strong adaptation potential to future climate. This SNP-based core collection represents a unique and viable working asset for accelerated traits-discovery, in the species and should play a pivotal role in international collaborative initiatives dedicated to promoting C. olitorius use and conservation.